Twospotted Spider Mite, Tetranychus urticae Koch (Arachnida: Acari: Tetranychidae) - Thomas R. Fasulo; Harold A. Denmark (EDIS)
The twospotted spider mite, Tetranychus urticae Koch, has been controversial in its taxonomic placement. About 60 synonyms included under this species have compounded the controversy. The body of a spider mite is separated into two distinct parts: (1) the gnathosoma and (2) the idiosoma. The gnathosoma includes only the mouthparts. The idiosoma is the remainder of the body and parallels the head, thorax and abdomen of insects. After hatching from the egg, the first immature stage (larva) has three pair of legs. The following nymphal stages and the adult have four pairs of legs. This document is EENY-150 (originally published as DPI Entomology Circular 89), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: August 2000.